Effect of ethylene-diamine-tetra-acetic acid (dipotassium salt) and heparin on the estimation of packed cell volume - Pennock, C. A. (1966)
The effect of varying concentrations of ethylene-diamine-tetra-acetic acid (E.D.T.A.) (dipotassium salt) and heparin on the estimation of packed cell volume has been studied using a microhaematocrit method. Varying concentrations of E.D.T.A. can produce serious errors in estimation of packed cell volume (P.C.V.) and reliable results are only obtained within the range of 1 to 2 mg./ml. Heparin is a more suitable anticoagulant for this investigation as varying the concentration has little effect. Storage with either anticoagulant at suitable concentrations for 24 hours at room temperature has little influence on the results.